DNA Sequence and Comparison of Virulence Plasmids from Rhodococcus equi ATCC 33701 and 103 - Takai, Shinji (American Society for Microbiology, 2000)
The virulence plasmids of the equine virulent strains Rhodococcus equi ATCC 33701 and 103 were sequenced, and their genetic structure was analyzed. p33701 was 80,610 bp in length, and p103 was 1 bp shorter; their sequences were virtually identical. The plasmids contained 64 open reading frames (ORFs), 22 of which were homologous with genes of known function and 3 of which were homologous with putative genes of unknown function in other species. Putative functions were assigned to five ORFs based on protein family characteristics. The most striking feature of the virulence plasmids was the presence of a 27,536-bp pathogenicity island containing seven virulence-associated protein (vap) genes, including vapA. These vap genes have extensive homology to vapA, which encodes a thermoregulated and surface-expressed protein. The pathogenicity island contained a LysR family transcriptional regulator and a two-component response regulator upstream of six of the vap genes. The vap genes were present as a cluster of three (vapA, vapC, and vapD), as a pair (vapE and vapF), or individually (vapG; vapH). A region of extensive direct repeats of unknown function, possibly associated with thermoregulation, was present immediately upstream of the clustered and the paired genes but not the individual vap genes. There was extensive homology among the C-terminal halves of all vap genes but not generally among the N-terminal halves. The remainder of the plasmid consisted of a large region which appears to be associated with conjugation functions and a large region which appears to be associated with replication and partitioning functions.